The Language Politeness in The Novel Beauty And The Best by Luna Torashyngu - Mislamuddin, Mislamuddin; Wicaksono, Andri; Alfiawati, Riska; Damiri, Adenan (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This research aimed to investigate the language politeness in the novel "Beauty and The Best" by Luna Torashyngu". The research method uses descriptive qualitative with content analysis. The data source of this research is taken from "Beauty and The Best" novel by Luna Torashyngu. The results show six variations of language politeness in this novel. There are six maxims in this novel: the maxim of humility, the maxim of sympathy, the maxim of agreement, the maxim of praise, the maxim of generosity, and the maxim of wisdom. The conversation in the maxim of wisdom shows the attitude of wise figures in making speeches with their interlocutors from the maxims of politeness in language. Meanwhile, the speech shows politeness in the language in the maxim of generosity. Speakers in carrying out conversations can still uphold their generosity attitudes so that a conducive speech situation can still be created. In the maxim of praise, the conversations that are carried out also show perspectives of praising through their speech and in the maxim of agreement. On the contrary, speakers commit many violations, especially characters who act as antagonists. Likewise, there are also many deviations from the maxim of agreement, even though some show an utterance that creates an agreement between the speaker and the interlocutor.